A practical and highly sensitive C3N4-TYR fluorescent probe for convenient detection of dopamine. Issue 28 (29th June 2015) - Li, Hao; Yang, Manman; Liu, Juan; Zhang, Yalin; Yang, Yanmei; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : The C3 N4 -tyrosinase (TYR) hybrid is a highly accurate, sensitive and simple fluorescent probe for the detection of dopamine (DOPA). Abstract : The C3 N4 -tyrosinase (TYR) hybrid is a highly accurate, sensitive and simple fluorescent probe for the detection of dopamine (DOPA). Under optimized conditions, the relative fluorescence intensity of C3 N4 -TYR is proportional to the DOPA concentration in the range from 1 × 10 −3 to 3 × 10 −8 mol L −1 with a correlation coefficient of 0.995. In the present system, the detection limit achieved is as low as 3 × 10 −8 mol L −1 . Notably, these quantitative detection results for clinical samples are comparable to those of high performance liquid chromatography. Moreover, the enzyme-encapsulated C3 N4 sensing arrays on both glass slide and test paper were evaluated, which revealed sensitive detection and excellent stability. The results reported here provide a new approach for the design of a multifunctional nanosensor for the detection of bio-molecules.